Rancang Bangun Pembangkit Listrik Picohidro Curah Hujan - Pijar Nurofiq Pratama; Indra Riyanto; Suwasti Broto (FAKULTAS TEKNIK UNIVERSITAS BUDI LUHUR, 2023)
Indonesia has a fairly high rainfall of (2000-3000 mm per year) This has the potential to be used as an alternative energy source for power generation. In this final project, a picohydro power generation system was designed with energy sources derived from rainfall. The designed system consists of gutters with a height of 1 m, 1/2